2022
DOI: 10.1167/iovs.63.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor Manifestations of Primary Mitochondrial Optic Nerve Disorders

Abstract: Purpose To compare the manifestations of photoreceptors (PRs) in three hereditary optic neuropathies affected by primary mitochondrial dysfunction and discuss whether the retinal ganglion cells (RGCs) or the PRs are preferentially affected. Methods A retrospective analysis of patients with genetically confirmed diagnoses of optic neuropathies associated with mitochondrial dysfunction was performed. This cohort included Leber's hereditary optic neuropathy (LHON), autosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…1 B). Electrophysiological tests showed early optic nerve dysfunction followed by gradual loss of photoreceptor response as described in our previous study [ 8 ]. When the patient repeated exams by age 27, mid-peripheral retinal pigmentary changes appeared on fundus color photography and autofluorescence imaging (Fig.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…1 B). Electrophysiological tests showed early optic nerve dysfunction followed by gradual loss of photoreceptor response as described in our previous study [ 8 ]. When the patient repeated exams by age 27, mid-peripheral retinal pigmentary changes appeared on fundus color photography and autofluorescence imaging (Fig.…”
Section: Resultssupporting
confidence: 65%
“…Wide variability in phenotypes has been noticed in OPA13, and the SSBP1 genotype–phenotype correlations is not well-established yet. Among 60 published patients with missense SSBP1 variants, optic atrophy was present in 95% of them [ 4 8 ]. Sixty-five percent of patients had pigmentary changes on fundus photography, 57.8% presented with foveopathy on macular OCT, and 29.3% exhibited rod-cone degeneration on full-field ERG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, we observed that the ADHD model presents visual function impairment, with a deficit in the photoreceptors/bipolar cell circuits, and RGCs circuits. Thus, the impairment in these circuits demonstrates that the ADHD model has retinal function impairment that may be related to ADHD features, namely: distractibility and inattention [ 46 ] and reduced visual acuity [ 48 ], which are also described in ADHD children and adolescents [ 49 , 50 ]. However, we did not detect any alterations in the photopic b-wave in the ADHD conditions, which suggests that the bipolar cell’s function impairment is less subtle when the retina is light-adapted.…”
Section: Discussionmentioning
confidence: 99%